Against Pogge's 'Cosmopolitanism'. (26th June 2013) - Steinhoff, Uwe
Abstract: Thomas Pogge labels the idea that each person owes each other person equal respect and concern 'ethical cosmopolitanism' and correctly states that it is a 'non‐starter'. He offers as an allegedly more convincing cosmopolitan alternative his 'social justice cosmopolitanism'. I shall argue that this alternative fails for pretty much the same reasons that 'ethical cosmopolitanism' fails. In addition, I will show that Pogge's definition of cosmopolitanism is misleading, since it actually applies to ethical cosmopolitanism and not to social justice cosmopolitanism. This means that cosmopolitanism as defined by Pogge is wrong in the light of his own arguments and that Pogge is not even a cosmopolitan in the sense of his own definition. I will further show that he is also not a cosmopolitan if cosmopolitanism is defined as a philosophical position involving the claim that state borders have no fundamental moral significance.